2023
DOI: 10.3389/fmed.2023.1057685
|View full text |Cite
|
Sign up to set email alerts
|

Post-LASIK dry eye disease: A comprehensive review of management and current treatment options

Abstract: Laser-assisted in situ keratomileusis (LASIK) is a unique corneal stromal laser ablation method that uses an excimer laser to reach beneath corneal dome-shaped tissues. In contrast, surface ablation methods, such as photorefractive keratectomy, include removing epithelium and cutting off the Bowman’s layer and the stromal tissue of the anterior corneal surface. Dry eye disease (DED) is the most common complication after LASIK. DED is a typical multi-factor disorder of the tear function and ocular surface that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 201 publications
0
3
0
Order By: Relevance
“…Postoperative corneal epithelial thickening could be a mechanism of early myopic regression after LASIK surgery [ 19 , 20 ]. In addition, postoperative dry eye disease caused by LASIK could damage the ocular surface and change the corneal epithelial structure [ 21 ]. In addition to epithelial proliferation, the forward shift in corneal curvature could be another etiology of early myopic regression [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative corneal epithelial thickening could be a mechanism of early myopic regression after LASIK surgery [ 19 , 20 ]. In addition, postoperative dry eye disease caused by LASIK could damage the ocular surface and change the corneal epithelial structure [ 21 ]. In addition to epithelial proliferation, the forward shift in corneal curvature could be another etiology of early myopic regression [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of laser ablation on the cornea may trigger a wound healing process that causes proliferation of the corneal epithelium 21 . In addition, postoperative dry eye disease after LASIK can damage the ocular surface and alter the structure of the corneal epithelium 22 . In previous research, the corneal epithelium was shown to proliferate in the presence of high levels of inflammatory cytokines such as growth factor and insulin-like growth factor-1 23 , 24 , which also exist in the cornea after the LASIK procedure 25 .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the laser ablation may induce the wound-healing process of the cornea and thereby contribute to corneal epithelium proliferation [ 22 ]. Additionally, the existence of postoperative dry eye following the LASIK surgery could impair the ocular surface and change the corneal epithelium structure [ 23 ]. In relation to the molecular pathway, corneal epithelium proliferation was observed under high-level inflammatory cytokine expression such as growth factors and insulin-like growth factor-1 [ 24 , 25 ], which were present in the cornea after the LASIK surgery [ 26 ].…”
Section: Discussionmentioning
confidence: 99%